Metabolites induced by citrus tristeza virus and ‘Candidatus Liberibacter asiaticus’ influence the feeding behavior of Diaphorina citri: an electrical penetration graph and LC–MS/MS study - Jingtian Zhang; Fengchun Xia; Yuhe Li; Yangyang Liu; Fengnian Wu; Xiaoling Deng; Meirong Xu (Phytopathology Research)
Abstract Citrus Huanglongbing and Citrus tristeza are two diseases that affect the citrus industry worldwide. The pathogens causing these diseases are the phloem-limited bacteria ‘Candidatus Liberibacter spp.’ (mainly Ca. L. asiaticus, CLas) and citrus tristeza virus (CTV). We recently found that both CLas and CTV could be acquired and retained by the Asian citrus psyllid Diaphorina citri. However, the mechanism through which CLas and CTV interact with the insect vectors and plant hosts has not been defined. In this study, an electrical penetration graph was used to study the feeding behavior of D. citri adults on four groups of Citrus reticulata Blanco cv. Hongjü plants: healthy, CLas-infected, CTV-infected, and CTV-CLas coinfected plants. Liquid chromatography with tandem mass spectrometry (LC–MS/MS) was applied to analyze the metabolites of the four groups of plants. The combined results are as follows: (1) The lowest number of metabolites were enriched in CTV-infected plants, which hardly influenced the feeding behavior of D. citri, suggesting that mild CTV strain (CT31) infection caused limited disorders in citrus plants compared with CLas infection; (2) Increased levels of L-arabinose and kaempferol in CTV-infected and CLas-CTV coinfected plants were suggested to contribute to increased penetration time during feeding of D. citri. CLas-infection increases the difficulty of finding appropriate feeding sites by the vector and results in xylem feeding for certain duration; (3) A significant reduction in α-linolenic acid metabolism in CLas-infected plants was found to be related to methyl jasmonate signaling, which induced resistance to D. citri and increased the duration of salivation. This effect was reversed by coinfection with CTV and was consistent with the phloem structure and carbohydrate accumulation alteration; (4) Stress response-associated 2'-hydroxygenistein and sakuranetin were highly upregulated flavonoid in CTV-CLas coinfected plants. This combinged with the anatomical alterations might interfere with D. citri feeding in the citrus phloem, as reflected by the time reduction of sap-sucking there. These findings will provide new insights into the interactions between CTV and CLas in citrus and the insect vector D. citri that transmiting these pathogens.